2009
DOI: 10.2320/matertrans.m2009247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mechanical Vibration on Cooling Rate and DAS of AC4C Aluminum Alloy Gravity Die Castings

Abstract: Gravity die casting of AC4C aluminum alloy with mechanical vibration (0-120 Hz) was conducted. Columnar rod specimens (25 mm  L210 mm) were cast to investigate the effect of mechanical vibration on the cooling rate and the dendrite arm spacing of AC4C aluminum alloy castings. The cooling rate increased by imposition of the mechanical vibration, and increased with the increase of the vibration frequency. When the mechanical vibration imposed, the mold temperature increased quickly and reached higher temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 16 publications
(14 reference statements)
3
7
0
Order By: Relevance
“…It is worth mentioning here that similar effect was observed with mechanical vibrations by Omura et al (2009), who reported that the cooling rate of melt increased by imposition of mechanical vibrations, and this effect increased with increasing the vibration frequency. It is believed that the acoustic streaming, which homogenizes the melt temperature, and enhances the convectional heat transfer at the mold wall, plays a role in this effect.…”
Section: Resultssupporting
confidence: 80%
“…It is worth mentioning here that similar effect was observed with mechanical vibrations by Omura et al (2009), who reported that the cooling rate of melt increased by imposition of mechanical vibrations, and this effect increased with increasing the vibration frequency. It is believed that the acoustic streaming, which homogenizes the melt temperature, and enhances the convectional heat transfer at the mold wall, plays a role in this effect.…”
Section: Resultssupporting
confidence: 80%
“…During ultrasound treatment, the eutectic solidification time grew about 10% longer compared with that without ultrasound treatment. It is worth mentioning here that a similar effect was observed with mechanical vibrations by Omura et al (2009), who reported that the cooling rate of melt increased by imposition of mechanical vibrations, and this effect increased with increasing the vibration frequency [9]. It is believed that the acoustic streaming, which homogenizes the melt temperature, and enhances the convectional heat transfer at the mold wall, plays a role in this effect [6][7][8].…”
Section: Methodssupporting
confidence: 59%
“…It was reported that the effect of fluid flow could be equivalently related with heat transfer calculation by changing thermal conductivity . The temperature gradient of the solidification front will be reduced when the thermal conductivity of the liquid phase is increased, which enhances the local undercooling in liquid and then leads to the formation of equiaxed grain in the solidification front.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…Since it is difficult to evaluate the vibration induced convection in the liquid directly and combine it with the FD‐CA model, the effect of MV in the present model was assessed from the aspects of changing the thermal conductivity of the liquid and increasing the nucleation probability. Taking the data that used to represent the thermal conductivity of the liquid with electromagnetic stirring as reference, a two‐times higher thermal conductivity was assumed as the effective thermal conductivity in liquid with MV due to a micro‐scale oscillating flow. Meanwhile, a 10% larger nucleation probability was also assumed to characterize the increased nucleation sites due to dendrite fragmentation.…”
Section: Numerical Modelingmentioning
confidence: 99%